EVALUASI PELAKSANAAN PROGRAM KAMPUS MENGAJAR: SEBUAH LITERATUR REVIEW - Dewi, Fatimah Candrawati; Retnawati, Heri (Jurnal Evaluasi Pendidikan, 2024)
Kampus Mengajar is one of the teaching assistance program activities part of the MBKM. Kampus Mengajar has two main outputs, namely developing the ability of program participants (students) to improve leadership skills, develop creativity and innovation, solve problems, communicate, manage groups and improve analytical skills for thinking. Outcomes for schools are focused on improving literacy and numeracy skills. This research is a literature review to examine the evaluation results of several evaluation articles on the implementation of the Kampus Mengajar collected from various indexed journal sources for the last 4 years. Based on the results of the study it can be concluded that this program has many positive effects. This effect can be felt by all parties concerned. This program also has obstacles, the existence of obstacles is expected to be used as learning for partners involved in the Kampus Mengajar.